(untitled) (Cambridge, UK, 2002)
This theoretically inspired study explores legislative politics in Argentina, Brazil, Chile, and Mexico. Instead of beginning with an assumption that these legislatures are either rubber-stamps or obstructionist bodies, the chapters provide new data and a fresh analytical approach to describe and explain the role of these representative bodies in these consolidating democracies. For each country the book provides three chapters dedicated, in turn, to executive-legislative relations, the legislatures' organizational structure, and the policy process.
Keywords: Legislative bodies,Legislative power,Executive power,Party discipline,Cơ quan lập pháp,Quyền lập pháp,Quyền hành pháp,Kỷ luật Đảng; Latin America,Latin America,Latin America,Latin America